Evaluating the Impact of Insecurity on Nigeria’s National Development Since the Fourth Republic - Akindoyin, Dare Isaac; Obafemi, Akintomiwa Olaniyi (African Journal of Stability and Development (AJSD), 2025)
This study critically evaluates the impact of insecurity on Nigeria’s national development; it explores the interplay between persistent security challenges and the country’s socio-economic progress. Nigeria, Africa’s most populous nation and largest economy, has grappled with diverse security threats, including terrorism, insurgency, banditry, kidnapping, communal clashes, and herders-farmers conflicts. These threats have not only destabilised communities but also disrupted economic activities, strained governmental resources, and exacerbated social inequalities. Utilising the descriptive approach, the research explores the direct and indirect implications of insecurity on critical areas of Nigeria’s national development. It highlights how insecurity has deterred foreign direct investment, displaced populations, and weakened institutional capacities, further entrenching poverty and unemployment. The study also examines the socio-political dimensions of insecurity, including its role in fostering corruption, eroding trust in governance, and undermining Nigeria’s democratic consolidation. Drawing on secondary qualitative sources from government reports, academic literature, and field studies, the research argues that addressing insecurity requires holistic and inclusive strategies that integrate military responses with socioeconomic reforms, community engagement, and regional cooperation. The study finds that increment of public spending on security, weakening of state institutions and loss of public trust in governance are some of the economic and socio-political impacts of insecurity on Nigeria’s national development. The study concludes that to alleviate the effects of insecurity on national development, it is imperative to tackle the underlying reasons of discontent, such as poverty, inequality, and ineffective governance in Nigeria.